LANGUAGE STYLES USED IN EDUCATIONAL ADVERTISEMENT OF THE JAKARTA POST NEWSPAPER - Rifka Fani Syuhada; Iskandar Abdul Samad; Kismullah Abdul Muthalib (English Education Journal, 2020)
The educational advertisements are displayed in various media: printed or electronic media. The advertisements are set in many types, forms, and styles of the language used to persuade customers. However, they have not been clearly investigated yet until there are no certain determinates to these cases, especially, the language styles use. This research aims to describe the styles of language in the educational advertisement of The Jakarta Post newspaper published from May 2018 to August 2019. The theory used in this study was put forward by Moriarty, Mitchell, and Wells (2012). This research used a descriptive qualitative method. The results showed that there were three language styles from twenty-four advertisements that appeared in the educational advertisement on The Jakarta Post newspaper. These were hard-sell style, straightforward style, and the combination of hard-sell and straightforward. However, the most dominant language style appearing in the educational advertisement of The Jakarta Post newspaper in May 2018 to August 2019 edition was a hard-sell style because the language style of this advertisement provided detailed information in which it is very often used in displayed advertisements.